2010
DOI: 10.1021/la101688v
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Zein Microphases in Ethanol−Water

Abstract: Zein, a major protein of corn, is soluble in binary mixtures of ethanol and water. It has an amphiphilic character and is capable of self-assembly into nano- and microsized rods, spheres, and films upon solvent evaporation. The formation of microspheres is of particular interest for the development of delivery systems. Control over structure formation requires a better understanding of zein behavior in solution. The objective of this work was to investigate the effect of zein concentration and the effect of et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(106 citation statements)
references
References 40 publications
5
100
0
1
Order By: Relevance
“…All other reagents were of analytical grade. Zein nanoparticles were prepared by the solvent evaporation method (Wang & Padua, 2010) following the procedure reported in a previous study (Soltani & Madadlou, 2014). Briefly, zein powder was dissolved (2 mg mL -1 ) in 80% v/v aqueous ethanol solution and stirred at 700 rpm for 15 min at 25°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All other reagents were of analytical grade. Zein nanoparticles were prepared by the solvent evaporation method (Wang & Padua, 2010) following the procedure reported in a previous study (Soltani & Madadlou, 2014). Briefly, zein powder was dissolved (2 mg mL -1 ) in 80% v/v aqueous ethanol solution and stirred at 700 rpm for 15 min at 25°C.…”
Section: Methodsmentioning
confidence: 99%
“…An exemplar SEM image of nanoparticles is shown in Figure 1 The surface tension of zein particles dispersion was ~28 mN m -1 indicating particles high affinity to locate on hydrophile-hydrophobe phases interface and reduce their contact area. This property is given by the amphiphilic nature of zein (Wang & Padua, 2010). All the zein-based Pickering emulsions prepared with different oil/aqueous phases ratios were however unstable considerably and broken down in <45 min.…”
Section: Pickering Emulsionsmentioning
confidence: 99%
“…The previously mentioned results revealed that particle formation in this study may be different from the cases reported before, in which ethanol evaporation induced layer-by-layer adsorption of zein to a central core or nucleus. 39,40 The layer-by-layer assembly requires a long time and slow ethanol evaporation without stirring, and thus burst nucleation and uniform particle growth would be less likely to occur.…”
Section: Insight Into Formation Of Zein Nanoparticles Timescale Of Pamentioning
confidence: 99%
“…6 The zein storage proteins are frequently found in maize endosperm, where they are deposited as protein bodies within the rough endoplasmic reticulum. 7,8 Zeins are renewable, biodegradable, biocompatible, and nontoxic. They have more hydrophobic than hydrophilic amino acids in their structure, making them insoluble in water, which is a requirement for the preparation of water-based formulations.…”
Section: Introductionmentioning
confidence: 99%